The effect of Vitex Agnus-Castus pill on follicles number and size in infertile women with polycystic ovary syndrome: A triple-blind placebo randomized clinical trial - Vahideh Behmard; Fatemeh Hadizadeh- Talasaz; Maryam Pishvaee; Nasim Khajavian; Roghayeh Rahmani Beilandi (Mashhad University of Medical Sciences, 2022)
Introduction: Polycystic ovary syndrome (PCOS) is the most common cause of ovulation disorder in women of childbearing age, with a prevalence of 20% worldwide. Due to the increasing tendency to use herbal medicines, this study was performed aimed to investigate the effect of Vitex Agnus-Castus pill on the number and size of follicles in infertile women with polycystic ovary syndrome. Methods: This triple-blind clinical trial study was performed in 2020-2021 on 60 infertile women with polycystic ovary syndrome. Subjects were randomly assigned to the intervention (Vitex Agnus-Castus) and control (placebo) groups. The intervention group used two Vitex Agnus-Castus tablets and one Folic Acid daily and the control group used two placebo tablets and one Folic Acid tablet for two months. In the second month, in addition to the mentioned drugs, all participants from the third to the seventh day of menstruation used 2.5 mg Letrozole for five days and on the 13 day of the cycle, they referred for ultrasound. Data were analyzed using SPSS software (version 16) and Chi-square and Mann-Whitney tests. P<0.05 was considered statistically significant. Results: After the intervention, the mean number of follicles in the Vitex Agnus-Castus group was significantly higher than the control group (2.73 ±0.90 vs. 2.06 ± 0.98, P = 0.008). Also in the Vitex Agnus-Castus group, the mean size of follicles was significantly higher than the control group (19.71± 1.98 vs. 17.73 ± 3.44, P = 0.009). Conclusion: The use of Vitex Agnus-Castus tablets along with Letrozole in comparison with Letrozole alone can improve the quality of follicles.